Features of Neurohumoral Relations in Diastolic Dysfunction of the Heart in Adolescents with Myocardial Pathology - L.F. Bohmat; V.V. Nikonovа; S.R. Tolmachevа; T.S. Vvedenskaia (Zaslavsky O.Yu., 2015)
It is found that only in adolescents with I type left ventricular diastolic dysfunction, there is a significant activation of sympathoadrenal system, and in patients with type II and III, increasing activation of the renin-angiotensin-aldosterone system is detected. Among the factors leading to the progression of left ventricular diastolic dysfunction, the components of the renin-angiotensin-aldosterone system, especially aldosterone, play the largest role.